When Is the Vestibular Aqueduct Enlarged? A Statistical Analysis of the Normative Distribution of Vestibular Aqueduct Size - Vijayasekaran, S.; Halsted, M.J.; Boston, M.; Meinzen-Derr, J.; Bardo, D.M.E.; Greinwald, J.; Benton, C. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The size of vestibular aqueducts (VAs) seen on CT studies varies. The current practice of calling a VA enlarged when it exceeds a certain threshold (eg, 1.5 mm at the midpoint) is arbitrary. Our hypothesis was that statistical analysis of the range of VA widths in a normal-hearing population would lead to a mathematic definition of the upper-limit-of-normal VA width.Materials and METHODS: The VA midpoint and opercular widths were measured in 73 children with normal hearing. Statistical analysis yielded values of the 99th, 97.5th, 95th, 90th, 75th, and 50th percentiles for this normal distribution.RESULTS: The upper-limit-of-normal (95th percentile) values for the VA midpoint and opercular widths were 0.9 and 1.9 mm, respectively. The VAs with greater widths may reasonably be considered enlarged.CONCLUSION: The VAs with midpoint or opercular widths of 1.0 and 2.0 mm or greater, respectively, are enlarged.